Adherence to antiretroviral therapy, CD4 count, viral load and opportunistic infections in people with HIV/AIDS: a cross-sectional study - Nursalam, Nursalam; Sukartini, Tintin; Misutarno, Misutarno; Priyantini, Diah (Universitas Airlangga, 2024)
Introduction: Globally, antiretroviral therapy (ART) has been successful in reducing the death rate due to human immunodeficiency virus (HIV). Different conditions in Indonesia mean the death rate due to HIV/AIDS is still high. The problem lies in the low compliance with ART. This study aimed to analyze the correlation between ART adherence with number of CD4, the opportunistic infection (OI) and viral load in PLHIV. Methods: A quantitative survey with cross-sectional approach was conducted between August – September 2022. As many as 375 PLHIV were recruited and agreed to give consent as research respondents. All respondents completed a questionnaire about ART adherence, OI and had blood taken to check CD4 count and viral load. Analyses were performed using Chi-squared test SPSS version 21 with significance level p<0.05. Results: A significant relationship was shown between ART adherence and OI (p value= 0.000 with <0.05). The respondents who reported adherence in ART also showed asymptomatic OI. The analysis also showed that ART adherence had significant relationship with CD4 count (p value= 0.000 with <0.05) and viral load (p value= 0.000 with <0.05), respectively. Respondents adherent to taking ART had better level of CD4 and suppressed viral load in the body. Conclusions: Adherence of antiretroviral therapy is the important factor contributing to the immune status of PLHIV, which has an impact on reducing CD4 count and suppressing viral load, thereby preventing the emergence of OI.